Análise do dimensionamento de pessoal de enfermagem em unidade de terapia intensiva para adultos - Inoue, Kelly Cristina (2008)
The dimensioning of the nursing staff in the Intensive Care Unit (ICU) aims at providing favorable working conditions for taking care of seriously ill patients, with lower risks for the staff's and their patients' health. In order to have an adequate dimensioning in the ICU it is also necessary to quantify the workload of nursing so as the several particular activities in charge of this sector may be considered. In doing so, the Nursing Activities Score (NAS) has been developed and it is available for use in the Brazilian context. Furthermore, concerning the nursing workload measure it is necessary to consider the minimum criteria established by the COFEN Resolution # 293/2004, such as the Technical Security Rate (TSR) and the proportion of nurses over the totality of the nursing staff. As a result of noticing some workload of the nursing team in a ICU for adults (ICU-A) of a School Hospital of the Northwest of Paraná, this research study was carried out in an effort to analyze the dimensioning of the nursing staff of the ICU-A, according to the nursing workload obtained by the NAS instrument and the criteria established in the COFEN Resolution # 293/2004. It is a descriptive exploratory study which consisted of 107 patients/clients who were placed in the ICU-A for at least 24 hours between November 13, 2007 and May 15, 2008. The data was daily collected by filling in an instrument consisting of three parts: Data of the Patient and of the Submit, NAS and, the Proportion of the Nursing Professionals in Relation to the Number of Patients. Microsoft Office Excel 2003 and Statistics 8.0 were used in order to manage and analyze the data. This research is registered upon the Written Opinion # 412/2007 from the Ethical Permanent Committee of Research with Human Beings (EPCHB) of the State University of Maringá. Out of the results the score of NAS was obtained for all the patients and on the day it varied from 479.7 to 1007.2 scores, with an average of 697.3 scores (DP ± 83.5) and a median value of 687.0 scores. Basing on the average of staff estimated by NAS (n=7) and following the COFEN Resolution # 293/2004, it was evidenced that the staff team of the ICU-A should have 40 nursing professionals, from which 21 (52.5%) should be nurses divided into five work teams. It was verified that there is a deficit of 12 (30%) workers and the proportion of nurses (35.7%) is below the expected number. Finally, it showed as evidence that there is a lack of nursing professionals in the ICU-A, particularly, due to the fact that in this sector, complex activities are done and/or they are not considered in the traditional dimensioning methods. As to solve or reduce this problem, the daily use of NAS in a predictive way is recommended in order to adequate the work demand and the number of nursing professionals.